Joox Media to Improve Students' Listening Skill - Aminina, Irena; Candraloka, Olyvia Revalita; Shofiyuddin, Muh (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aimed to find out the effectiveness of Joox media in improving listening skill in eleventh grade at MAN 2 Jepara in academic year 2022/2023. This study was conducted at the eleventh grade students’ of MAN 2 Jepara which consist of 76 students. The method used in this study was true experimental research with pre-test post-test control group design. To collect the data, the researcher used pre-test and post-test in the form of missing word. Then, the students need to fill the missing word while listening to the song. The result showed that the mean score of students in experimental class was 82.77 while the mean score of students in control class was 77.08. The T-test analysis showed that t-test result was more than t-table (2.051 1.666) and the value of Levene’s test of equality variances was 0.04 which was less than 0.05. This result indicated that the use of Joox media was effective to improve students listening skill.